Global Reproductive Health: Perspectives, Challenges, and Future Directions - Blanco, Dennis V. (Animo Repository, 2016)
The paper conducts a synthesis integrative review of the existing literatures about the various local perspectives on contemporary issues, challenges, lessons and opportunities that several countries around the world confront with regards to reproductive health program and services. Using the public policy approach, the paper seeks to create a global perspective synthesis on reproductive health experiences in the context of policy issues, policy opportunities, and policy- making dimension. In the end, the paper found out that global reproductive health programs and services issues included an interplay of culture and ethnicity, socio-economic status, tradition, religion, language research, education, and equity and quality challenges while policy-direction challenges and opportunities encompasses a more devolved primary health clinics and hospitals, funding for research on sexual and reproductive health, developing a framework for indicators on health care, civil society engagement, reproductive health education , reproductive health as a matter of human right as well training and professionalization of reproductive health service providers.